Śniegi Północy i Słońce Wschodu. Rola przestrzeni naturalnej w procesie kształtowania fikcyjnego świata w literaturze fantasy - Ratajczyk, Jakub Ścibor (Przestrzenie Teorii, 2025)
The article is dedicated to the issue of space and nature in the context of worldbuilding theory and its impact on narrative structures in literature. The analysis focuses on the ways literary worlds are constructed and the role that space and nature play within them. The study is based on Mark J.P. Wolf’s concept, which distinguishes four spheres of fictional reality construction (nominal, cultural, natural, and ontological). Particular attention is given to the topographical turn and geopoetics, which emphasize the significance of place and landscape in narration. The case study examines A Game of Thrones and A Clash of Kings by George R.R. Martin, where geographical space determines the culture and beliefs of fictional societies. Two contrasting areas of the fictional world are discussed – the harsh, snowy, and forested North of Westeros and the hot, steppe and desert-like lands of Essos. The paper also highlights how space and nature contribute to creating the novel’s distinctive atmosphere and their impact on the text’s appeal to readers.